2019
DOI: 10.1364/ol.44.002903
|View full text |Cite
|
Sign up to set email alerts
|

Controlling group and phase velocities in bidirectional mode-locked fiber lasers

Abstract: A bidirectional mode-locked fiber laser producing two correlated frequency combs of the same repetition rate is demonstrated. The intensity dependence of pulse and phase velocities are measured simultaneously. As expected, the phase delay is determined by the linear and nonlinear indices of refraction. The nonlinear Kerr effect contribution to the pulse velocity is dwarfed by a contribution from saturable gain dynamics.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Summarily, bidirectional ring Er-doped fibre laser, mode-locked by carbon nanotube saturable absorber and nonlinear polarisation evolution, in a steady-state generates near transform-limited 790 and 570-fs soliton pulses at 1555 nm central wavelength and 14.78 MHz repetition rate in both directions 33 . The phenomenon of identical central wavelengths of counter-propagating solitons refers to the colliding modelocking 34,35 . The output power was 1 mW in a clockwise direction, and 0.4 mW in a counter-clockwise direction.…”
Section: Resultsmentioning
confidence: 99%
“…Summarily, bidirectional ring Er-doped fibre laser, mode-locked by carbon nanotube saturable absorber and nonlinear polarisation evolution, in a steady-state generates near transform-limited 790 and 570-fs soliton pulses at 1555 nm central wavelength and 14.78 MHz repetition rate in both directions 33 . The phenomenon of identical central wavelengths of counter-propagating solitons refers to the colliding modelocking 34,35 . The output power was 1 mW in a clockwise direction, and 0.4 mW in a counter-clockwise direction.…”
Section: Resultsmentioning
confidence: 99%
“…However, it has been demonstrated that this traditional definition of group velocity does not apply to media with saturable gain/absorption [ 25 ]. In a fiber laser, energy exchanges between the leading and trailing edge of the envelope determine its velocity [ 26 ]. The situation is similar in the laser with intracavity etalon: at each round-trip, a small portion of energy of each pulse of a bunch is transferred to the next one.…”
Section: Auto-synchronization Of Parent and Nested Cavitymentioning
confidence: 99%
“…This nonlinearity can be exploited for making pulsed lasers and sensors of very small energy consumption. It would also avoid the nonlinearities that affect the group and phase velocities in fiber based sources of frequency combs [4]. The grey regions in Figs.…”
Section: Measurementsmentioning
confidence: 99%
“…By 1953 image transmission through the first fiberscope was demonstrated [1]. Today, optical fiber has become an integral part of many fields including telecommunication [2], medical [3], and metrology [4].…”
Section: Introductionmentioning
confidence: 99%